2009
DOI: 10.2516/ogst/2009013
|View full text |Cite
|
Sign up to set email alerts
|

Cold Start on Low Compression Ratio Diesel Engine: Experimental and 3D RANS Computation Investigations

Abstract: Résumé -Démarrage à froid d'un moteur Diesel à bas taux de compression : investigations expérimentales et numériques RANS tridimensionnelles -Les futures normes d'émission concernant les moteursDiesel imposent une réduction importante des émissions polluantes à la source, avant les dispositifs de post-traitement. La réduction de "production" de NOx en maintenant de très bas niveaux d'émission de suie, de HC et de CO doit être effectuée sans dégrader le confort de conduite et en contrôlant la consommation de ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…• C [4] and for future applications with reduced compression ratio ( [4,5,6,7]) these aids are necessary below 10…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…• C [4] and for future applications with reduced compression ratio ( [4,5,6,7]) these aids are necessary below 10…”
Section: Introductionmentioning
confidence: 99%
“…Studies performed on climatic chambers ( [3,8,9,10]) have certainly delivered valu-able information but several measurement uncertainties and the incapability of using extra diagnostic tools have prevented from making a detailed explanation of this combustion process. Laget et al [6] show a more systematic approach to the problem in which in-cylinder analysis, endoscopic visualization and CFD modeling are coupled in order to identify the pre-glowing glow plug duration, nozzle tip protrusion, injector spray angle and cranking speed as key parameters with influence on startability. Later, a more detailed analysis of the combustion sequence have been presented by Perrin et al [11], in which the location of the first ignition spots are shown to appear in the vicinity of the glow plug, together with the influence of some other parameters like swirl motion and injection pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Desantes et, al., [7] conducted a full description of the processes associated with engine ignition using in-cylinder high speed imaging. Laget, Pacaud and Perrin [8] also have used video imaging in addition to regular in-cylinder experimentation, and computational analysis for describing the diesel engine cold start at low compression ratio. The effect of low compression on the diesel engine cold start behavior was the main objective of the work conducted by MacMillan [9].…”
Section: Introductionmentioning
confidence: 99%
“…As a reference to poor ignition conditions, Broatch et al [5] report that a lightduty diesel engine (CR 18:1) can start without aid at temperatures as low as −11 • C. At lower temperatures, ignition aids become necessary. In future applications, in which compression ratio is reduced [6,7,8] to comply with the near future emissions standards [9,10], starting aids will be necessary at ambient temperatures below 10 • C (tested in a 14:1 CR engine [5]). These facts evidence the necessity of improving knowledge about combustion under low temperature cold start conditions in order to overcome present and future limitations of diesel engines for passenger cars.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, more systematic approaches aiming at engine cold start optimization have been reported. For example, Laget et al [7] combined in-cylinder pressure analysis, endoscopic visualization and CFD modeling in order to identify the pre-glowing period, nozzle tip protrusion, injector spray angle and cranking speed as key parameters with influence on startability. [15] presented a more detailed analysis of the combustion sequence in which the location of the first ignition spots are shown to appear in the vicinity of the glow plug, together with the influence of some other parameters like swirl motion and rail pressure.…”
Section: Introductionmentioning
confidence: 99%